Genetic, pathologic, and radiographic correlations in multiple sclerosis - Yates, R (2016)
Substantial evidence suggests that cortical tissue injury plays a key role in the progression of permanent disability in multiple sclerosis (MS). A greater knowledge of factors that drive pathology in the MS cortex is therefore desperately needed in order to develop novel medicines that can ameliorate disease burden in the progressive stage. In the current thesis, we undertake a robust and quantitative analysis of motor cortical neuropathology in a large cohort of post-mortem MS cases. We find that genetic variation at the HLA-DRB1 locus is associated with the extent of cortical demyelinating and inflammatory disease, especially in younger cases. Relevant to cortical neurodegeneration, we identify fibrinogen deposition as a novel component of MS cortical pathology that associates with neuronal loss, show that carriage of HLA- DRB1*15 has a critical impact on the relationship between microglia/macrophage inflammation and cortical neuronal density, and demonstrate disease-relevant changes to motor cortical neuronal glutamic acid decarboxylase expression. Given the myriad subcortical connections of the motor cortex, we have also undertaken an extensive assessment of corticospinal tract lesional burden throughout the neuraxis and find that motor cortical neurodegeneration appears independent of subcortical tissue injury. Taken together, this thesis highlights the importance of genetic variation at the HLA- DRB1 locus to cortical pathologic outcome, and the fundamental contribution of fibrinogen deposition and cortical parenchymal inflammatory factors to neuronal fate.